Republic of Korea : 2008 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Korea. (IMF Staff Country Reports; Country Report, 2008)
The Republic of Korea's 2008 Article IV Consultation highlights that Korea's business cycle is turning downward while inflation pressures have increased. Risks are mainly external and on the downside, but a volatile domestic political environment also clouds the outlook. Inflation pressures have risen, largely owing to higher global commodity prices, but should ease as growth slows. Despite still solid export growth, higher commodity prices have led imports to rise even more sharply while the services account deficit remains sizable.